Properties of B.subtilis and Their Use in Clinical Practice - Yu.V. Marushko; M.H. Hrachova; Ye.Yu. Marushko (Zaslavsky O.Yu., 2015)
This paper summarizes the data on the properties of Bacillus subtilis and their use in clinical practice. The uniqueness of Subalin is due to the combination of bacilli ability to inhibit the growth of pathogenic and opportunistic microorganisms, and to produce interferon, thereby the drug shows antibacterial, antiviral and immunomodulatory action. Application of the drug in combination with antibiotic enables to achieve high clinical efficacy, maximum eradication of pathogens, to prevent further recurrences.